The role of three education centers in promoting entrepreneurship careers for vocational students - Timan, Agus; Maisyaroh, Maisyaroh; Wiyono, Bambang Budi; Adha, Maulana Amirul; Valdez, Anabelie Villa; Ariyanti, Nova Syafira (Journal of Education and Learning (EduLearn), 2024)
The potential for vocational students to achieve success in entrepreneurship is considerable, especially since they have acquired specific skills that are in line with their area of specialization since the beginning of their vocational schooling. However, schools cannot be alone in promoting entrepreneurial careers among vocational students. This study aims to measure the role of three educational centers, in influencing self-efficacy, entrepreneurial intention and career choice as an entrepreneur. This study was approached with a quantitative approach using structural equation modeling (SEM), the sample in the study was 354 vocational students. Data analysis through four stages, namely exploratory factor analysis, normality and outlier tests, confirmatory factor analysis and hypotheses testing (structural model). The results showed that the three education centers significantly influence selfefficacy and entrepreneurial intention which in turn can encourage students to choose a career as an entrepreneur. This research contributes to the understanding of how the three education centers can be an important catalyst in shaping a generation of resilient and innovative entrepreneurs.